PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH CALON JEMAAH HAJI DI BANK SYARIAH INDONESIA KC VETERAN MAKASSAR (Fakultas Dakwah dan Komunikasi, 2022)
This study aims to determine the service quality of the Indonesian Islamic Bank Veterans Branch Makassar, customer satisfaction of prospective pilgrims, and the effect of service quality on customer satisfaction of prospective pilgrims at Makassar Veterans Branch Office. The approach used in this research is the quantitative method. The sample used in this study was 308 customer respondents based on the Lomeshow formula if the sample was infinite or the time of the research was not known. The research was carried out in June 01-July 01 2021. The data collection used was using a questionnaire (questionnaire). The data collected were analyzed using multiple linear regression analysis with hypothesis testing using t-test and f-test. Based on the results of the t-test hypothesis, the study showed that the service quality variable was the service quality. Physical evidence 0.841 > 0.05 showed insignificant results, the empathy variable 0.114 > 0.05 showed insignificant results, the reliability variable 0.005 <0.05 showed significant results., Responsiveness 0.199 > 0.05 indicates insignificant results and Guarantee 0.670 > 0.05 indicates insignificant results, so based on the hypothesis in this study H0 is accepted and H1 is rejected, and the results of the f test value Fcount (2,351)>Ftable ( 0.446, sig value 0.041> 0.05 shows a significant result between service quality and customer satisfaction.